Kombinasi Arnold Cat Map dan Modifikasi Hill Cipher Menggunakan Kode Bunyi Beep BIOS PHOENIX - Elvis Pawan; Kaharuddin Kaharuddin; Dony Arius (STMIK PONTIANAK, 2019)
Safeguarding and securing a secret data is something that must be done either in personal, organizational, corporate or governmental data but not a few do not know how to secure data, especially in a message, so this research is conducted to provide a way to encrypt messages.In this research using a collaboration of the Hill Cipher algorithm and Arnold cat map, used to get maximum encryption results on data or messages. In its application, the Hill cipher algorithm will be modified using a bios phoenix sound code and image. Hill Cipher and Arnold Cat Map algorithms are suitable to be combined because it will produce strong enough encryption because the results of text-based encryption from the Hill Cipher algorithm will be encrypted again using the image-based Arnold Cat Map algorithm.This research resulted in the modification of a Hill Cipher algorithm and Arnold Cat Map in the encryption process and description to improve the security of data and information. Keywords— Hill Cipher, Arnold Cat Map, Cryptography, Steganography